Can Scientific-Based Learning Close the Gap in Understanding Science Concepts Between Underachiever and High-Achiever Students? - Prayitno, Baskoro Adi; Widoretno, Sri; Sugiharto, Bowo; Oetomo, Dwi (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
Teachers commonly employ inquiry learning, discovery, and group investigation in science education. However, there is limited research on the efficacy of these learning methods in reducing the disparity in students' scientific conceptual understanding between underachievers (UA) and high achievers (HA). The primary objective of this research was to assess the effectiveness of these learning methods in closing the disparity in scientific conceptual understanding among students. This research involved 192 twelfth-grade students (96 UA and 96 HA). Students were randomly assigned to four learning treatments: inquiry, discovery, group investigation, and varied lecture. Students took an essay test to measure their scientific conceptual understanding before and after the treatment. The gap in students’ scientific conceptual understanding was analyzed by examining the interaction between the learning methods and their academic abilities. The outcomes indicated no distinction in scientific conceptual understanding among the three treatment groups (inquiry, discovery, and group investigation). Nonetheless, variations in students' scientific conceptual understanding were observed in varied lecture learning settings. The study affirmed disparities in the comprehension of scientific concepts between UA and HA students across inquiry, discovery, and varied lecture learning. Interestingly, no variation in the understanding of scientific concepts was identified between UA and HA students in the context of group-investigation learning.